(untitled) (Nigerian Journal of Physiological Sciences, 2025)
Cohabitation represents a significant shift in family structures as they undergo demographic and economic transitions. This practice is a common phenomenon among Nigerian university undergraduates. Therefore, this study examined the demographic factors that determine cohabitation practices among undergraduates in Osun State, Nigeria. Guided by the individualization theory, the research design adopted was a survey, and questionnaire and in-depth interview instruments were used to collect the data. A sample of 400 respondents was included in the quantitative analysis, while 18 participants were included in the qualitative aspects of the analysis. Descriptive (frequency and percentages) and bivariate (chi-square test and correlation) were used to analyze the quantitative data, while the qualitative data were content analyzed. The findings revealed that a majority of the respondents have high (45.3%) knowledge of cohabitation practice, and pre-marital cohabitation (56.5%) is one of the major dimensions of cohabitation reported by the respondents. Determining factors adduced for engaging in cohabitation were the urge to be a ‘baby mama’ (77.5%) and economic benefits (74.5%); while 73.0% of them have a regular pattern of practicing cohabitation. About 42.0% of them have good perception, and less than 55% have a negative attitude towards cohabitation. A significant age difference in knowledge of cohabitation (χ2 = 96.96, ρ<0.01) and knowledge of cohabitation was positively correlated with attitude (r = 0.611, p<0.01) and perception (r = 0.528, p<0.01) among the respondents. Similarly, perception of cohabitation was positively correlated with attitude towards cohabitation (r = 0.187, p < 0.01). The implication of this finding is that high knowledge will lead to high perception and positive attitude towards disengaging from cohabitation practices. Adolescents and youths should be enlightened about the negative consequences of cohabitation relationships that may jeopardize their future endeavours.